Slovak Adaptation of the Coronavirus Anxiety Scale. Issue 2 (7th February 2023) - Pekárová, Veronika; Rajčániová, Eva; Tomšik, Robert
Abstract: This study examined the psychometric properties of the Slovak version of the Coronavirus Anxiety Scale (CAS-SK) in a sample of adult Slovaks ( N = 743). The data were collected online during the second wave of the COVID-19 pandemic in Slovakia. Along with the Coronavirus Anxiety Scale, the Perceived Stress Scale, and the Well-Being Index were administered to the respondents. The results of the Confirmatory Factor Analysis show a stable uni-dimensional structure of the CAS-SK, good reliability, and adequate convergent validity. The Item Response Theory findings suggest that all items have good discrimination parameters, all thresholds increased monotonically across the rating scale, and that the CAS-SK is more informative in individuals with a high level of coronavirus anxiety. These results suggest that the CAS-SK is a valid and reliable tool for measuring coronavirus anxiety.